Sistem Agribisnis Usaha Ternak Itik di Desa Slorok Kecamatan Doko Kabupaten Blitar - Siti Azizah (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2022)
Livestock agribusiness is an integrated part of agricultural development in meeting the animal protein needs of the community. The development of the livestock agribusiness system must be supported by the performance of the subsystems in it. Ducks are potential poultry to produce eggs and meat in Slorok Village, Doko District, Blitar Regency. The study aimed to determine the agribusiness system for duck farming, which is useful for developing livestock business in the future. The research results will help formulate policies in Sorok Village for the development of livestock businesses based on the potential problems in the duck agribusiness system.Studies on activities and policies in the duck farming subsystem, namely input, rearing management, product processing, marketing, and trade, are needed to improve the duck agribusiness system at the research site. This research was conducted from June to January 2022 using qualitative descriptive analysis. The selection of informants used the key informant method and further informants were determined using the snowball technique of informants considers duck agribusiness's experience and knowledge in Slorok Village. Based on the study results, the four agribusiness subsystems are not yet related, and their existence is still partial and not integrated. The livestock development policy in Slorok Village at the upstream sub-system level is thus aimed at improving feed, capital, coaching, mentoring for bargaining power in determining prices at the level of collectors or final consumers.